Novel technique to prepare LiTaO3 at low temperature - Muthurajan, H.; Kumar, H. H.; Natarajan, N.; Ravi, V. (Ceramics International, 2008)
Firstly, fresh tantalum hydroxide was precipitated from TaF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing lithium and tantalum hydroxides together and heating at a low temperature (450 degrees C) produced pure ultrafine single phase LiTaO3 (LT). This is the lowest temperature so far reported for the formation of LT in the literature. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by transmission electron microscopy (TEM). (c) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical synthesis X-ray diffraction; Electron microscopy; electronic materials; LiTaO3